Mechanism of interactions between endoplasmic reticulum stress and autophagy in hypoxia/reoxygenation-induced injury of H9c2 cardiomyocytes - Guan, Gaopeng (Mol Med Rep, 2019)
Endoplasmic reticulum (ER) stress and autophagy are involved in myocardial ischemia-reperfusion (I/R) injury; however, their roles in this type of injury remain unclear. The present study investigated the roles of ER stress and autophagy, and their underlying mechanisms, in H9c2 cells during hypoxia/reoxygenation (H/R) injury. Cell viability was detected by CCK-8 assay. The autophagy flux was monitored with mCherry-GFP-LC3-adenovirus transfection. The expression levels of autophagy-related proteins and ER stress-related proteins were measured by western blotting. Apoptosis was detected by flow cytometry and western blotting. The results indicated that autophagy was induced, ER stress was activated and apoptosis was promoted in H9c2 cells during H/R injury. The inhibition of ER stress by 4-phenylbutyrate or C/EBP homologous protein (CHOP)-targeting small interfering RNA (siRNA) decreased autophagy and ameliorated cell apoptosis during H/R injury. Activation of autophagy by rapamycin attenuated ER stress and ameliorated cell apoptosis. Inhibition of autophagy by 3-methyladenine or Beclin1-targeting siRNA aggravated ER stress and exacerbated cell apoptosis, and activation of ER stress by thapsigargin decreased autophagy and induced cell apoptosis. Collectively, the findings of the present study demonstrated that H/R induced apoptosis and autophagy via ER stress in H9c2 cells, and that CHOP may serve an important role in ER stress-induced autophagy and apoptosis. Autophagy, as an adaptive response, was activated by ER stress and alleviated ER stress-induced cell apoptosis during H/R injury.